Insomnia Levels In Elderly At Griya Santo Yosef And Panti Surya Before And After The Lavender Aromatherapy Treatment - Maharani, Sagung P; Hadi, Wiyono; Mellow, Prettysun A (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: The process of aging that occurs in elders will decrease their physiology functions, such as their lack of sleep, both timewise and quality-wise. This situation will cause sleep problems in elders, such as insomnia. Insomnia could be treated by using both pharmacology and non-pharmacology. Lavender aromatherapy treatment is one of the nonpharmacology relaxation therapies that could help manage insomnia in older adults. Aim: Knowing the difference of insomnia levels before and after the lavender aromatherapy treatment in elders. Methods: This examination is using Quasi Experiment of the treatment group and the control group. Furthermore, the idea of this experiment is to use a pre-test and post-test control group design approach. For sample earnings, consecutive sampling technique is used by picking a sample that is qualified for inclusion criteria, and that is not included in the exclusion criteria. Thus, the minimum sample could be fulfilled. The statistics test is using a Chi-Square test. Result: The result of insomnia level before and after aromatherapy treatment using the ChiSquare analysis (p=0,000) shows that there isa difference that is due to the intervention. In the treatment group, there were 14 participants with mild insomnia and seven participants with severe insomnia. The result shows that 14 participants did not have insomnia, and seven other participants have mild insomnia. Meanwhile, the control group shows no difference in their insomnia, but decreasing in their score. Conclusion: Elders with lavender aromatherapy treatment for one week have shown declining insomnia level from severe to mild, and for the mild level of insomnia problems become cured, However, those who were given placebo shows no difference.